Keragaman Genetik dan Karakter Agronomi Galur-galur Kacang Bogor (Vigna subterranea L. Verdc.) Hasil Seleksi Galur Murni Asal Lanras Sukabumi - Yuliawati; Wahyu, Yudiwanti; Surahman, Memen; Rahayu, Arifah (JURNAL AGRONIDA, 2019)
Bambara groundnut is a legume plant that has several advantages, including drought tolerance, has ability to grow on infertile land and high nutrient content. The production of bambara groundnut is still low, so it is necessary to obtain high yielding bambara groundnut line. The experiment was conducted to evaluate the genetical variation and agronomic characters of 30 bambara groundnut lines. This experiment was carried out in experimental field of SEAMEO BIOTROP Tajur Bogor (± 280 m above sea level), on Februari-June 2018. Plant materials used in this research were 30 bambara groundnut lines derived from pure line selection of Sukabumi landrace and unselected Sukabumi landrace uses as control. The experiment was arranged in a randomized complete block design with three replications. Results showed that there were variations among several agronomic characters of bambara groundnut lines. Several lines showed superior characters. R59.30, A90.8, A41.4, A56.10, A43.5, A103.5, A41.4, A55.8, R59.31 and A28.10 lines were lines with the higest dry pods weight compared to the other lines and control line. These lines had potential as new superior varieties of bambara groundnut. Keywords: landrace, new superior variety, pure line selection